Vulnerabilities, Threats and Attacks on SCADA, Mobile Networks and in IoT - P, Latha; Pallavi, Andhe (International Journal of Computer Sciences and Engineering, 2025)
Ever since the emergence of 1G in mobile technology, evolution of new mobile generations have introduced various protocols and interfaces, high data transmission capacity making way for different vulnerabilities which allows for launch of attacks on network components. Performance of mobile networks and security is of a major concern. Industrial networks and automation networks were isolated in a physical sense until the emergence of Supervisory Control and Data Acquisition (SCADA). Simplicity, more productivity, reduction in downtime for system adjustments are some advantages with the industrial networks going public on internet. The result is the increase in the number of attack vectors on the SCADA system. IoT to define is a transformative approach providing numerous services over internet. Integrating the existing smart devices to the internet introduces security issues, threat of cyber attacks and crime. In this paper, we discuss the various vulnerabilities, threats and attacks on these three systems namely Mobile networks, SCADA systems, and IoT systems.